Critical Thinking Skills in Solving Hots-Based Procedural Text Problems for Class X Students at Senior High School - Ramdayani; Yunidar; Asrianti; Ida Nur'aeni; Juniati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Higher-level thinking competencies are one of the main competencies in HOTS-oriented learning. However, studies on these competencies in high school students in solving text-based problems are still limited, especially those that relate student achievement to the causative factors. The procedural text was chosen as an assessment context because it demands an understanding of the logical sequence, cause-effect relationship, and correctness of steps, making it relevant to measure students' analytical, evaluative, and reasoning abilities. This study aims to describe these competencies in solving HOTS-based procedural text problems and identify the factors that affect them. The study used a qualitative descriptive approach with 23 subjects from class X B Senior High School. Data was collected through tests, interviews, and documentation, then analyzed using Miles and Huberman's interactive models. The instrument is adapted from the Facione framework of interpretation, analysis, inference, and evaluation with the addition of creation indicators as HOTS operational indicators. The results show that student achievement is generally in the good category, with analysis as the most dominant aspect, while interpretation, inference, evaluation, and especially creation still need to be improved. The difference in achievement was influenced by the understanding of text structure, reading literacy, and teacher learning strategies. These findings confirm the need for Indonesian language teachers to consistently integrate HOTS-based activities to develop students' ability to analyze, evaluate, and create, while contributing to the development of HOTS-oriented Indonesian language education.